Librarian Service Management to Improve Students’ Reading Interest: A Case Study at SDN 22 Panai Hulu - Carles Harahap; Inom Nasution; Yahfizham Yahfizham (Journal of General Education and Humanities, 2025)
This study aims to analyse librarian service management in increasing students' reading interest at SDN 22 Panai Hulu. The research was motivated by the low level of reading interest among elementary school students, which is influenced by several factors such as limited access to engaging reading materials and the growing impact of digital distractions, particularly social media. Using a descriptive qualitative approach, the study involved eight purposively selected participants, including the school principal, librarian, administrative staff, and students. Data were collected through interviews and observations, then analysed using Miles and Huberman’s model, which includes data condensation, data display, and conclusion drawing. The findings indicate that optimising library functions, creating a comfortable and engaging reading environment, and addressing literacy challenges in the digital era are critical strategies in fostering students' reading interest. Librarians play a proactive role in curating relevant books and organising literacy programs that appeal to students. The study concludes that effective librarian service management can significantly improve reading motivation, and school libraries must continue adapting to technological advancements to fulfil the evolving literacy needs of students.